2008
DOI: 10.1038/sj.bjc.6604449
|View full text |Cite
|
Sign up to set email alerts
|

Association of size at birth with adolescent hormone levels, body size and age at menarche: relevance for breast cancer risk

Abstract: Birth size has been positively associated with age at menarche and height in adolescence and adulthood, but the relevant biological mechanisms remain unclear. Among 262 Norwegian term-born singleton girls, birth size measures (weight, length, ponderal index, head circumference and subscapular skin-fold thickness) were analysed in relation to adolescent hormone levels (oestradiol, prolactin, dehydroepiandrosterone sulphate, androstenedione and free testosterone index), age at menarche and adolescent (ages 12.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 27 publications
6
27
0
1
Order By: Relevance
“…Similar to previous studies [38], we observed that height was significantly associated with increased risk of breast cancer in urban women. We did not observe this association for rural women, possibly because of low prevalence of taller women in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies [38], we observed that height was significantly associated with increased risk of breast cancer in urban women. We did not observe this association for rural women, possibly because of low prevalence of taller women in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…To bear children early, a woman needs to cease stature growth and reach menarche early [49]. To do this, a whole suite of hormonal and growth changes are required several years earlier [41,50,51]. Thus, phenotypic specialization needs to be underway by middle childhood if very early childbearing is going to be possible.…”
Section: Flexibility In Reproductive Timing: Proximate Explanationsmentioning
confidence: 99%
“…Currently, existing studies have mainly focused on personal and demographic characteristics, such as obesity and social conditions, as the potential factors influencing the timing of menarche (Roberts et al, 1977;Adair, 2001;Adair and Gorden-Larsen, 2001;Freedman et al, 2002Freedman et al, , 2003Hesketh et al, 2002;Castelo-Branco et al, 2006;Ibanez et al, 2006;Opdahl et al, 2008). Only a few studies have examined exposures at the time of organogenesis, even though fetal programming of the timing of menarche is likely (Vatten et al, 2003;Windham et al, 2004;Axmon, 2006).…”
Section: Introductionmentioning
confidence: 99%